2011
DOI: 10.1007/s12678-011-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modifications of a Carbon Anode Catalyst by Control of Functional Groups for Vitamin C Fuel Cells

Abstract: We report that electro-oxidation treatment of carbon paper generates specific functional groups, and controllable coating of metal oxide films on carbon surface alters capacitive behaviors. Electrochemical characteristics, I-V curves in fuel cells, and a structural analysis of XPS represent that the carboxyl group is the most effective functional group in an electro-oxidation of L-ascorbic acid. The appropriate film thickness of titania on electro-oxidized carbon electrode further increases fuel cell performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The trend in activity for Vitamin-C electro-oxidation was expected to be similar to the capacitance trend, and this was found to be the case but with the exception of ATC-3. It has been shown previously that the surface oxygen intensity is important in improving electro-catalytic activity to the electro-oxidation of Vitamin-C [18,21,24] . However, ATC-3 was found to have a smaller O/C ratio than that of ATC-5, yet the electrocatalytic activities of both samples were similar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trend in activity for Vitamin-C electro-oxidation was expected to be similar to the capacitance trend, and this was found to be the case but with the exception of ATC-3. It has been shown previously that the surface oxygen intensity is important in improving electro-catalytic activity to the electro-oxidation of Vitamin-C [18,21,24] . However, ATC-3 was found to have a smaller O/C ratio than that of ATC-5, yet the electrocatalytic activities of both samples were similar.…”
Section: Resultsmentioning
confidence: 99%
“…The final criterion for the preparation of catalysts is their successful application as electrode materials in a fuel cell system with a zero-gap configuration [18] . Since this energy conversion system is considered as a potential energy source for implantable medical devices, testing was carried out at a temperature of 36.5 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several AAOR electrocatalysts have been investigated, including noble metals [12,13], TiO 2 [14], polymers [2,15,16], porphyrins [17,18], and high-surface-area carbon black [11,19,20]. Our group previously reported that carbon black (BP2000) is the most effective AAOR electrocatalyst [11].…”
Section: Introductionmentioning
confidence: 99%